2000
DOI: 10.1557/proc-639-g3.8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the GaN epilayer quality using in-situ reflectance measurements

Abstract: Although a tremendous amount of work has been done these last years on the nitride semiconductor system, a lot is still to be understood regarding the growth mechanisms of GaN. The standard GaN MOCVD growth process includes the low temperature deposition of a nucleation layer, followed by an anneal at high temperature, and the GaN layer is then deposited. The number of process parameters which can be used to tune the growth is very large (temperatures, times, thicknesses, molar flow rates and ratios …) and, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Sumiya et al found that adding H 2 to the annealing ambient enhanced the evaporation and reduced the NL surface coverage [37]. Finally, no change or influence in the NL evolution was observed for changes in the NL growth T [35], and similar results were reported in Section 4.2.…”
Section: Comparison To Previous Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Sumiya et al found that adding H 2 to the annealing ambient enhanced the evaporation and reduced the NL surface coverage [37]. Finally, no change or influence in the NL evolution was observed for changes in the NL growth T [35], and similar results were reported in Section 4.2.…”
Section: Comparison To Previous Resultssupporting
confidence: 64%
“…This is particularly true if different NL thicknesses are optimized, because the thicker NLs will likely have faster decomposition rates but require more time for recrystallization compared to thinner NLs [32]. The P at which the NL is annealed has been shown to influence the reflectance waveform [34], leading to rougher NLs at high P. The relative H 2 , N 2 , and NH 3 flows during annealing also influence the NL evolution [35][36][37]. For example, Halidou et al have shown that when NLs are annealed in H 2 and NH 3, a dramatic decrease in the optical reflectance is observed, indicating a rough morphology.…”
Section: Comparison To Previous Resultsmentioning
confidence: 99%
“…The adopted solution is to take advantage of the very small roughness induce on such micro-electronic manufactured devices. Indeed, Ruffenach-Clur et al [32] have focused on process parameters involved in the GaN MOCVD growth process. At the end of the process, the rms rugosity Rq of the GaN sample was found to be 177nm.…”
Section: Tab 4 -Spectral Bands and Opacity Region (Emission Layer In ...mentioning
confidence: 99%